Arecoline-induced pro-fibrotic proteins in LLC-PK1 cells are dependent on c-Jun N-terminal kinase. (17th February 2016) - Lin, Sheng-Hsuan; Chiou, Shean-Jaw; Ho, Wan-Ting; Chuang, Chao-Tang; Chuang, Lea-Yea; Guh, Jinn-Yuh
Abstract: Areca nut (AN) chewing is associated with chronic kidney disease (CKD). However, the molecular mechanisms of AN-induced CKD are not known. Thus, we studied the effects of arecoline, a major alkaloid of AN, on proximal tubule (LLC-PK1) cells in terms of cytotoxicity, fibrosis, transforming growth factor-β (TGF-β) and c-Jun N-terminal kinase (JNK). We found that arecoline dose (0.1–0.5 mM) and time (24–72 h)-dependently induced cytotoxicity without causing cell death. Arecoline (0.25 mM) also time-dependently (24–72 h) increased fibronectin and plasminogen activator inhibitor-1 (PAI1) protein expressions. Arecoline (0.25 mM) time-dependently (24–72 h) increased TGF-β gene transcriptional activity and supernatant levels of active TGF-β1. Moreover, arecoline (0.25 mM) activated JNK while SP600125 (a JNK inhibitor) attenuated arecoline-induced TGF-β gene transcriptional activity. SP600125, but not SB431542 (a TGF-β receptor type I kinase inhibitor), attenuated arecoline-induced fibronectin and PAI1 protein expressions. Finally, tubulointerstitial fibrosis occurred and renal cortical expressions of fibronectin and PAI1 proteins increased in arecoline-fed mice at 24 weeks. We concluded that arecoline induced tubulointerstitial fibrosis in mice while arecoline-induced TGF-β and pro-fibrotic proteins (fibronectin, PAI1) are dependent on JNK in LLC-PK1 cells.